Advancing immunotherapy for esophageal cancer: decoding the roles of PD-L1, TME, and tumor-intrinsic biomarkers - Ma, Jiakang; Wu, Dangrou; Liu, Yongxuan; Zhang, Guangping (Frontiers in Immunology, 2025)
Esophageal squamous cell carcinoma (ESCC) remains a global health challenge, with immune checkpoint inhibitors (ICIs) reshaping therapeutic strategies. However, heterogeneous responses underscore the urgent need for robust predictive biomarkers. While PD-L1 expression remains the most widely used marker, its limitations, including spatial heterogeneity and inducible expression, have prompted exploration of alternative and composite indicators. Recent advances highlight the predictive potential of tumor immune microenvironment (TME) features such as tumor-infiltrating lymphocytes (TILs), tertiary lymphoid structures (TLSs), stromal maturity, and T cell–inflamed gene expression profiles. Concurrently, tumor-intrinsic biomarkers, including microsatellite instability, tumor mutational burden, neoantigen load, and chromosomal alterations—have shown promise in stratifying immunotherapy responders. Multi-omics approaches, liquid biopsies, and integration of host factors such as gut microbiota are emerging to refine patient selection. This review comprehensively examines evolving biomarkers and therapeutic trials, emphasizing the need for integrative precision strategies to optimize immunotherapy efficacy in ESCC.